Comportamiento agronómico de cinco hortalizas de hojas con tres abonos orgánicos en el centro experimental “La Playita”, de la Universidad Técnica de Cotopaxi - La Maná. - Montero Yánez, Irene Narcisa (2013)
This research was conducted at the Centre Experimental "La Playita", of the Technical University of Cotopaxi, La Maná Canton. WGS 84 geographic location: latitude S0 ° 56' 27 "Length W 79 ° 13' 25", height 220 meters above sea level. The research lasted for 120 days of field work, general objective was to determine the agronomic performance of five leafy vegetables with three organic fertilizers in the Centre Experimental "La Playita", of the Technical University of Quito - La Mana. The specific objectives were to: assess agronomically five vegetable leaves with organic fertilizers. Compare the use of organic fertilizers in the production of vegetables of the treatments in study. Set the level of profitability of the organic production of vegetables of treatments to study.Leafy vegetables and fertilizers that were used in the research in the experimental Center "La Playita" were: H1 chard, H2 turnip, H3 broccoli, collards H4, H5 purple cabbage and witness. Fertilizers: A1, 100 Vermicompost, 100% A2% water hyacinth and A3 50% 50% Vermicompost water hyacinth. A complete block at random (DBCA) with five vegetables with three organic fertilizers and three repetitions and a witness.The results were: in the last harvest in the cultivation of chard treatment given witness (technology of the farmer) won the largest number of sheets with 3.93 leaves; for the length of sheet treatment chard worm Humus water hyacinth achieved the highest average with 45.87 cm, as well as the width of sheet with 13.67 cm................................